Analisis Pengaruh Merek Dagang Internasional pada Produk Fashion - Ramadhan Bayu Prakoso; Dwi Imroatus Shilikah (Masyarakat Ekonomi Syariah Bogor, 2026)
Intellectual Property Rights (IPR) as an international issue have experienced rapid development. Intellectual property rights are rights derived from the creative activities of human intellectual abilities expressed to the public in various forms. The purpose of this study is to analyze the influence of international trademarks on fashion products. This research was conducted using a normative juridical approach combined with a qualitative method to analyze the impact of international trademarks on fashion products in relation to the basic principles of Intellectual Property Rights. The study shows that international trademarks have a significant influence on fashion products. The influence of trademarks on purchasing decisions can be seen through various aspects, such as product quality, brand image, price, and brand usage. Brand image has a positive effect on purchasing decisions for fashion products. Product quality is also an important factor in purchasing decisions, meaning that brands with competitive quality in the market obtain greater advantages in attracting consumers. In addition, price is also an influential factor in purchasing decisions for fashion products. Brand usage can also affect consumer interest in using fashion products. In the legal context, trademarks can also protect the rights of fashion design and products.